1993
DOI: 10.1021/bi00069a006
|View full text |Cite
|
Sign up to set email alerts
|

Structures of the noncovalent complexes of human and bovine prothrombin fragment 2 with human PPACK-thrombin

Abstract: Both human and bovine prothrombin fragment 2 (the second kringle) have been cocrystallized separately with human PPACK (D-Phe-Pro-Arg)-thrombin, and the structures of these noncovalent complexes have been determined and refined (R = 0.155 and 0.157, respectively) at 3.3-A resolution using X-ray crystallographic methods. The kringles interact with thrombin at a site that has previously been proposed to be the heparin binding region. The latter is a highly electropositive surface near the C-terminal helix of thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
118
2

Year Published

1994
1994
2008
2008

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 107 publications
(130 citation statements)
references
References 47 publications
10
118
2
Order By: Relevance
“…In PgdK1, NOES are observed between Trp25 and Tyr50, consistent with the two peptide strands crossing over each other although without proper P-sheet formation. Finally, in contrast to the case for tPA/K2 [33, 361, uPA/K [37, 671, and Ptb/K2 [30], we have uncovered no evidence for a-helical segments in Pgn/Kl. Neither has an a-helix been observed in the crystallographic structures of b-Ptb/Kl [29] and PgdK4 [31] nor in the solution structures of Pgn/K4 [34, 351.…”
Section: Comparison Of /%Sheets and Hairpin Turns In Kringlescontrasting
confidence: 96%
“…In PgdK1, NOES are observed between Trp25 and Tyr50, consistent with the two peptide strands crossing over each other although without proper P-sheet formation. Finally, in contrast to the case for tPA/K2 [33, 361, uPA/K [37, 671, and Ptb/K2 [30], we have uncovered no evidence for a-helical segments in Pgn/Kl. Neither has an a-helix been observed in the crystallographic structures of b-Ptb/Kl [29] and PgdK4 [31] nor in the solution structures of Pgn/K4 [34, 351.…”
Section: Comparison Of /%Sheets and Hairpin Turns In Kringlescontrasting
confidence: 96%
“…In addition, Fbg bound to [ANS]FPRmeizothrombin-des-F1 with a K D value of 25 M and was competitively displaced by Hir 54 -65 (SO 3 Ϫ ), which bound with a K D value of 27 nM, in agreement with independent binding studies. 2 These results were in keeping with crystallographic studies of the thrombin-F2 complex (14,61) and meizothrombindes-F1 (56), which concluded that F2 does not cover exosite I or interfere directly with the active site. Meizothrombin-des-F1, which contains F2 covalently attached, has activity toward tripeptide chromogenic substrates, but little activity toward clotting of Fbg (62).…”
Section: Discussionsupporting
confidence: 59%
“…Exosite I binds fibrinogen (Fbg) 1 (3), fibrin I and II (3,4), the 12-residue carboxyl-terminal hirudin 54 -65 sequence (5,6), thrombomodulin (7), the thrombin receptor (8,9), and an acidic sequence on the serpin, heparin cofactor II (10,11). Exosite II binds heparin and other glycosaminoglycans (2,12,13), prothrombin activation fragment 2 (F2) (14), the chondroitin sulfate moiety of thrombomodulin (15,16), the leech peptide hemadin (17), and an exosite II-specific human monoclonal antibody (18). Factors V (19 -22), Va (21,22), and VIII (19), platelet glycoprotein Ib␣ (23)(24)(25), and the snake venom protein bothrojaracin (26) have been reported to interact with both exosites I and II.…”
mentioning
confidence: 99%
“…One of these cationic exosites is the fibrinogen recognition site (Fenton, 1981(Fenton, , 1986, whereas the other is most likely the heparin binding site (Church et al, 1989;Karshikov et al, 1992;Arni et al, 1993). The fibrinogen exosite lies between surface loops Leu 33-Leu 41 and Arg 67-Lys 81 with Lys 109-Lys 110 nearby.…”
Section: Activation Domainmentioning
confidence: 99%